Pelatihan Guru SMA Dalam Menggunakan AI untuk Menyusun Materi, Menerapkan Strategi, dan Melaksanakan Asesmen - Widhiyanto Widhiyanto; Ardhi Prabowo; Christianti Tri Hapsari; Ira Mutiaraningrum; Candradewi Wahyu Anggraeni; Muhimatul Ifadah; Mohammad Ali Yafi (Jurnal Surya Masyarakat, 2025)
Digital transformation in education requires teachers to adapt to technological advancements, including AI. The integration of AI in teaching and learning offers great potential for creating a more personalized, interactive, and relevant learning experience. However, research shows that the use of AI in secondary schools is still limited because of a lack of understanding and skills among teachers. This Community Service Program (PKM) focuses on enhancing the competencies of teachers at SMAN 12 Semarang by integrating artificial intelligence (AI) technology into teaching. Through training, this program aims to equip teachers with the knowledge and practical skills to utilize AI to develop instructional materials, implement innovative learning strategies, and conduct effective assessments. The methods used include lectures, discussions, demonstrations, and practical training. The methodology employed in this study is a case study. Thirty-three teachers from various subjects participated in this activity. The survey results were analyzed using the mean, standard deviation, and thematic analysis. The survey results indicated that teachers had a positive outlook on using AI to create instructional materials, questions, and assessments. Teachers created AI chatbot prompts that were clear, specific, contextually relevant to learning, and outcome-oriented. This activity has proven to enhance high school teachers' literacy and skills in utilizing AI to create more meaningful and effective learning experiences.